EFFECT OF TREATED WATER WITH POLYMERIC BIGUANIDE (VANTOCIL IB), UPON THE ERITHROCYTE PARAMETERS AND TOTAL PLASMA PROTEINS OF BROILERS EFEITO DA ÁGUA TRATADA COM BIGUANIDA POLIMÉRICA (VANTOCIL IB) SOBRE O QUADRADO ERITROCITÁRIO E PROTEÍNAS PLASMÁTICAS TOTAIS DE FRANGO DE CORTE - Dirson Vieira (Pesquisa Agropecuária Tropical, 2007)
<!-- @page { margin: 2cm } P { margin-bottom: 0.21cm } --> The aim of the present work was to evaluate the effect of treated water with polymeric biguanide (Vantocil IB), with different dilutions, upon the erithrocyte parameters and total plasma proteins of broilers. Five treatments and four repetitions were carried out, with a total of 200 broilers. Group 1: not treated water - negative witness; Group 2: sodium hypoclorite with treated water (0.4 - 0.6 ppm) - positive witness; Group 3: polymeric biguanide treated water (Vantocil IB - 1:2000); Group 4: polymeric biguanide treated water (Vantocil IB - 1:4000); Group 5: polymeric biguanide treated water (Vantocil IB - 1:6000). The experimental unit was represented by ten broilers, and the experiment was conducted from July to August, 1995, during 42 days. At the end blood was spooned by puncture cardiac of one broiler of each group. The total plasma proteins was quantified for refratometric method, the average of the treatments did not differ statistically (p < 0.05) for the Tukey Test. KEY-WORDS: Blood; erithrocyte parameters; total plasma proteins. <!-- @page { margin: 2cm } --> <!-- @page { margin: 2cm } P { margin-bottom: 0.21cm } --> O objetivo do presente trabalho foi o de avaliar o efeito do tratamento da água com biguanida polimérica (Vantocil IB), em diferentes diluições, sobre o quadro eritrocitário e proteínas plasmáticas totais de frangos de corte. Foram ensaiados cinco tratamentos e quatro repetições, com um total de 200 aves. Grupo 1 - Água não tratada - testemunha negativa; Grupo 2 - Água tratada com hipoclorito de sódio (0,4 - 0,6 ppm) - testemunha positiva; Grupo 3 - Água tratada com biguanida polimérica (Vantocil IB - 1:2000); Grupo 4 - Água tratada com biguanida polimérica (Vantocil IB - 1:4000); Grupo 5 - Água tratada com biguanida polimérica (Vantocil IB - 1:6000). A unidade experimental foi representada por 10 aves, sendo o experimento conduzido no período de julho a agosto de 1995, com duração de 42 dias. Ao final foi colhido sangue por punção cardíaca de uma ave submetida a cada um dos cinco tratamentos. A proteína plasmática total foi dosada pelo método de refratometria, sendo que as médias dos tratamentos não diferiram estatisticamente (p < 0,05) pelo teste de Tukey. PALAVRAS-CHAVE: Sangue; parâmetros eritrocitários; proteínas plasmáticas totais. <!-- @page { margin: 2cm } -->